Neuroendoscopic Aspiration of Blood Clots in the Cerebral Aqueduct and Third Ventricle During Posterior Fossa Surgery in the Prone Position. Issue 2 (28th November 2018) - Feletti, Alberto; Stanzani, Riccardo; Alicandri-Ciufelli, Matteo; Giliberto, Giuliano; Martinoni, Matteo; Pavesi, Giacomo
Abstract: BACKGROUND: During surgery in the posterior fossa in the prone position, blood can sometimes fill the surgical field, due both to the less efficient venous drainage compared to the sitting position and the horizontally positioned surgical field itself. In some cases, blood clots can wedge into the cerebral aqueduct and the third ventricle, and potentially cause acute hydrocephalus during the postoperative course. OBJECTIVE: To illustrate a technique that can be used in these cases: the use of a flexible scope introduced through the opened roof of the fourth ventricle with a freehand technique allows the navigation of the fourth ventricle, the cerebral aqueduct, and the third ventricle in order to explore the cerebrospinal fluid pathways and eventually aspirate blood clots and surgical debris. METHODS: We report on one patient affected by an ependymoma of the fourth ventricle, for whom we used a flexible neuroendoscope to explore and clear blood clots from the cerebral aqueduct and the third ventricle after the resection of the tumor in the prone position. Blood is aspirated with a syringe using the working channel of the scope as a sucker. RESULTS: A large blood clot that was lying on the roof of the third ventricle was aspirated, setting the ventricle completely free. Other clots were aspirated from the right foramen of Monro and from the optic recess. CONCLUSION: We describe this novel technique, which represents a safe and efficient way to clear the surgical field at the end of posterior fossa surgery in the prone position. The unusual endoscopic visual perspective and instrument maneuvers are easily handled with proper neuroendoscopic training.